2017
DOI: 10.3904/kjim.2017.268
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing arterial pathologic changes affecting arteriovenous fistula patency and cardiovascular mortality in hemodialysis patients

Abstract: The radiocephalic arteriovenous fistula (AVF) provides optimal vascular access for hemodialysis; it has a higher long-term patency rate and fewer complications than other vascular access methods. However, the AVF has a high primary failure rate. The presence of small-diameter vessels at anastomosis sites is an important risk factor for AVF failure. However, in a recent study, despite selecting an adequate artery and vein for creating an AVF by routine preoperative vascular mapping, AVF maturation and primary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
0
17
1
Order By: Relevance
“…Lee et al . 23 reported that pre-existing arterial pathologic changes such as atherosclerosis affect not only the patency of vascular access but also increase the risk of cardiovascular mortality. These poor conditions of the vessel wall have an even greater effect when patients are concomitant with diabetes or coronary artery disease 22,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . 23 reported that pre-existing arterial pathologic changes such as atherosclerosis affect not only the patency of vascular access but also increase the risk of cardiovascular mortality. These poor conditions of the vessel wall have an even greater effect when patients are concomitant with diabetes or coronary artery disease 22,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous findings, maturation failure of AVF might be related to combined impacts of neointimal hyperplasia and unfavorable remodeling majorly owing to preexisting calcified vessels. In fact, these vascular pathologic changes increase both AVF failure rate and mortality rate in hemodialysis patients 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not possible for us to differentiate between the cause and effect of elevated USTIR artery and the corresponding arterial lesions. We know that pre-existing arterial disease results in poorer vascular access outcomes, 13 so the relevance of USTIR artery may warrant further investigation with a cohort of patients stratified according to pre-surgical levels of arterial disease.…”
Section: Discussionmentioning
confidence: 99%